2007
DOI: 10.1103/physrevd.75.115018
|View full text |Cite
|
Sign up to set email alerts
|

Connecting (supersymmetry) CERN LHC measurements with high scale theories

Abstract: If supersymmetry is discovered at the LHC, the measured spectrum of superpartner masses and couplings will allow us to probe the origins of supersymmetry breaking. However, to connect the collider-scale Lagrangian soft parameters to the more fundamental theory from which they arise, it is usually necessary to evolve them to higher scales. The apparent unification of gauge couplings restricts the possible forms of new physics above the electroweak scale, and suggests that such an extrapolation is possible. Even… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 94 publications
0
21
0
Order By: Relevance
“…In Ref. [52], it was demonstrated that the failure to infer even one soft mass experimentally may be sufficient to drastically alter the high-scale prediction for other masses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [52], it was demonstrated that the failure to infer even one soft mass experimentally may be sufficient to drastically alter the high-scale prediction for other masses.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [52] several invariants were introduced for the purpose of testing high-scale flavor universality in the presence of extra intermediate-scale GUT multiplets. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, they allow this hypothesis to be ruled out: measuring D B 13 = 0 or D L 13 = 0 at the low scale implies high-scale family non-universality; however, as noted in Ref. [33], measuring D B 13 = 0 and D L 13 = 0 at the low scale does not necessarily indicate high-scale universality. Current experimental data from flavor physics strongly motivates a flavor-universal mediation mechanism for SUSY-breaking.…”
Section: Flavor-blind Modelsmentioning
confidence: 99%
“…It would be very useful to have a method that allowed us to set bounds on the supersymmetry-breaking parameters at the messenger scale, independent of the unknown supersymmetry-breaking scheme and of the unknown value of the messenger scale. Renormalization Group Invariants (RGIs) [33]- [41] provide such a method. Determination of the value of the RGIs at the TeV scale sets their values at the messenger scale.…”
mentioning
confidence: 99%
“…On the other hand, the LHC has also searched for signals of new physics beyond the SM, either through the production of new particles or by looking for anomalous couplings for the SM particles [5]. However, so far current LHC studies have not detected any evidence of new physics, and the resulting bounds on the associated scale has been pushed into the TeV territory [6].…”
Section: Introductionmentioning
confidence: 99%